2020
DOI: 10.2422/2036-2145.201709_010
|View full text |Cite
|
Sign up to set email alerts
|

Volume rigidity ad ideal points of the character variety of hyperbolic 3-manifolds

Abstract: Given the fundamental group Γ of a finite-volume complete hyperbolic 3-manifold M , it is possible to associate to any representation ρ : Γ → Isom(H 3 ) a numerical invariant called volume. This invariant is bounded by the hyperbolic volume of M and satisfies a rigidity condition: if the volume of ρ is maximal, then ρ must be conjugated to the holonomy of the hyperbolic structure of M . This paper generalizes this rigidity result by showing that if a sequence of representations of Γ into Isom(H 3 ) satisfies l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This is a suitable adaptation of Mostow-Prasad rigidity to the context of representations. In a more general setting, Francaviglia and Klaff [FK06] proved some similar rigidity results for their definition of volume of a representation Γ → PO(m, 1), this time assuming m ≥ n ≥ 3 (the rigidity of volume actually holds also at infinity, as proved by Francaviglia and the second author [FS18] for the real hyperbolic lattices. Moreover, the second author also showed that the rigidity holds for complex and quaternionic lattices [Sav20]).…”
Section: Historical Backgroundmentioning
confidence: 66%
“…This is a suitable adaptation of Mostow-Prasad rigidity to the context of representations. In a more general setting, Francaviglia and Klaff [FK06] proved some similar rigidity results for their definition of volume of a representation Γ → PO(m, 1), this time assuming m ≥ n ≥ 3 (the rigidity of volume actually holds also at infinity, as proved by Francaviglia and the second author [FS18] for the real hyperbolic lattices. Moreover, the second author also showed that the rigidity holds for complex and quaternionic lattices [Sav20]).…”
Section: Historical Backgroundmentioning
confidence: 66%
“…They also show that the volume is rigid, that means |Vol(ρ)| ≤ Vol(Γ\H n ) and the equality holds if and only if ρ is conjugated to the standard lattice embedding, which is an equivalent formulation of Mostow rigidity. For sake of completeness we have to say that actually a similar result was proved for representations into PO(m, 1) with m ≥ n ≥ 3 by [FK06] and it remains valid even at ideals points of the PO(m, 1)character variety (see [FS18] for the case of real lattices and [Sav18] for the cases of complex and quaternionic lattices).…”
Section: Introductionmentioning
confidence: 59%
“…Some of these results rely on the notion of natural maps introduced by Besson, Courtois and Gallot [BCG95, BCG96, BCG98] and more precisely on the sharp estimate on the Jacobian of such maps. Actually the volume rigidity can be extended even at ideal points of the representations space, as proved by both Francaviglia and one of the authors [FS18,Sav18].…”
Section: Introductionmentioning
confidence: 84%